The Relationship of Age and Obesity with The Event of Preeclampsia in Pregnant Women - Dian Intan Permatasari; Triawanti Triawanti; Ari Yunanto; Syamsul Arifin; Edi Hartoyo (Lambung Mangkurat, 2023)
Preeclampsia is a hypertensive disease in pregnancy which is systolic/diastolic 140/90 mmHg and proteinuria 300 mg/24 hours after 20 weeks gestation. According to WHO in 2015, the incidence of preeclampsia was 0,51%-38,4%. In Indonesia, preeclampsia and eclampsia cause 30%-40% of maternal deaths. Age and obesity are part of the risk factors for preeclampsia. This study aims to determine the relationship between age and obesity with the incidence of preeclampsia in pregnant women. It was conducted by systematic review with Meta-Analysis. Number of articles identified were 8.073 articles and included in the meta-analysis for 15 articles with details of 6 articles for age variable, 4 articles for obesity variable, and 5 articles for age and obesity variables. The results show that there is a relationship with the incidence of preeclampsia in selected journals with a combined effect size value at age of 2,280; [95% Cl: 1,366-3,808, Z=3,151, p=0,002]; in obesity for 3,334; [95% Cl: 1,839-6,043, Z=3,968, p=0,000]. It can be concluded that there was a greater relationship between obesity and the incidence of preeclampsia with SD (OR=3,334) compared to Age with the incidence of preeclampsia in pregnant women with SD (OR=2,280).